(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This opening text introduces the different perspectives on dance dramaturgy that constitute this thematic dossier, highlighting the absence of a precise definition and the still sparse availability of discussions on dance dramaturgy. The text also presents how the various textual proposals have explored the theme of the dossier, presenting unique approaches to the subject, and connecting it to fields of knowledge in arts and humanities.